TEKNIK PEMERIKSAAN RADIOGRAFI KNEE JOINT DENGAN KLINIS OSTEOARTHRITIS DI INSTALASI RADIOLOGI RSUD DR LOEKMONO HADI KUDUS - Makiza Ignes Juvellin; Aninda Putri, Dita Amelia Putri, Fatwa Salsabila (CV. Adiba Aisha Amira, 2025)
Based on observations made by the author in June 2024 at the Radiology Installation of Dr. Loekmono Hadi Hospital, Kudus with clinical Osteoarthritis in the Knee Joint using conventional radiographic examination techniques with bilateral Antero Posterior (AP) and Lateral supine projections. This is different from the theory, namely the knee joint examination projection with clinical Osteoarthritis consists of AP projection, Lateral (Mediolateral) projection, AP/PA Weight-Bearing projection, and AP Oblique medial rotation projection (Bontrager, 2018). The purpose of this study was to determine the Knee Joint radiographic examination technique in clinical Osteoarthritis and to find out the reasons for the Knee Joint radiographic examination technique in clinical Osteoarthritis at the Radiology Installation of Dr. Loekmono Hadi Hospital, Kudus. The type of research used in compiling this scientific article is descriptive qualitative research with a case study approach. The time of data collection was June 2024. The data collection methods used included observation, interviews, and documentation. The subjects of the study were a patient and a radiographer at Dr. Loekmono Hadi Hospital. The data that has been obtained will be analyzed and changed into transcript form and then data reduction is carried out. Furthermore, the author reviews the existing literature and then draws a conclusion. The results of the study indicate that the Knee Joint examination technique in cases of Osteoarthritis in the Radiology Installation of Dr. Loekmono Hadi Hospital is carried out with AP Bilateral and lateral projections with the patient in a supine position. In the AP Bilateral projection, both knee joints are positioned in the middle of the image receptor and in the true AP position. While in the lateral projection, the knee joint is positioned true lateral with the right side on the image receptor with a flexion position of 20 ° and as a fixation the left leg is set forward. Lateral projections are carried out alternately for both legs. The image receptor used measures 35 x 43 cm. The vertical ray direction is perpendicular, the aiming point is 1.3 cm below the apex of the patella, FFD 100 cm. The exposure factor used in the AP projection is 60 kV 8 mAs and 60 kV 10 mAs for the lateral projection. The reason for performing a Knee Joint radiography examination in clinical Osteoarthritis is because it can produce a radiographic image that can help doctors evaluate the condition of the patient's genu in order to determine what medical action should be taken next.